Estimativa do relevo 3D do embasamento via inversão gravimétrica da porção nordeste do Pará, município de Salinópolis e entorno, com separação regional-residual utilizando Modelo GEMMA para profundidade da Moho - VIEIRA, Desirreé Cristine Pena (2019)
In this work we present the estimated basement relief of Pará Northeast, City of Salinópolis and the surrounding area. This estimated surface corresponds to the base of Pirabas formation and is obtained from gravity data and from gravity inversion technique. We used public gravity data from ANP and IBGE, however, to be used for estimating the basement relief, these data needed the treatment in respect of deep sources, specifically the separation of the contribution from the gravity anomaly produced by Moho. We conducted this separation using Moho relief depth of data available on GEMMA Project. We introduced on the gravimetric inversion, applied to these data, the prior information that the basement relief is characterized by smooth surface. This information is imputed by the global smoothness constraint, or first-order Tikhonov constraint, which introduces simultaneously stability to the estimation. In some locations of the studied area there is also available information about the depth of the basement obtained by wells. These wells also provide geological information of the layers arrangement in this area. Otherwise we do not have precise information about the density of the sedimentary package. But, as it is available such information of the depth of the basement, we made a systematic search in order to select the most effective density value. With this value of density selected, we proceed to estimate the relief of the basement of Pirabas Formation.